2020
DOI: 10.1021/acsanm.0c02176
|View full text |Cite
|
Sign up to set email alerts
|

Sonication Effectively Reduces Nanoparticle Size in Hemoglobin-Based Oxygen Carriers (HBOCs) Produced Through Coprecipitation: Implications for Red Blood Cell Substitutes

Abstract: Engineered hemoglobin (Hb) particles are O2 delivery vehicles that may be used as red blood cell (RBC) substitutes when blood is unavailable. One promising method produces high-purity Hb particles through coprecipitation with a removable inorganic template that yields porous Hb particles; however, this method traditionally results in particle diameters too large for applications in transfusion medicine. The current study investigates the incorporation of a sonication operation during Hb particle synthesis to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…These results are in agreement with the observations of the Palmer group. 43 Specifically, McDonel et al reported slight decreases in the size of Hb-NPs for the higher sonication values in terms of time and amplitude. However, in their study, the Hb-NPs were prepared by the coprecipitation, cross-linking, and dissolution method.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are in agreement with the observations of the Palmer group. 43 Specifically, McDonel et al reported slight decreases in the size of Hb-NPs for the higher sonication values in terms of time and amplitude. However, in their study, the Hb-NPs were prepared by the coprecipitation, cross-linking, and dissolution method.…”
Section: Resultsmentioning
confidence: 99%
“…However, in their study, the Hb-NPs were prepared by the coprecipitation, cross-linking, and dissolution method. 43 3.1.4. Characterization of Hb-NPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 86–88 ] As free Hb is unstable and has limited blood circulation times, efforts have been made to develop Hb‐based nanocarriers that could be used as an oxygen delivery system and a potential alternative for donor blood. [ 86,89 ] An MOF‐based system was first reported by Yu and co‐workers. They successfully encapsulated Hb within ZIF‐8 through biomimetic mineralization and prevented Hb from thermal‐, chemical‐, and biological degradation (Figure 4b).…”
Section: Mofs For Subcellular Structure Biopreservationmentioning
confidence: 99%